Bridging the Digital Gap: Empowering Women Entrepreneurs through Inclusive Development Communication - Meranti, Meranti; Lely Arrianie; Isna Silviana (Ikatan Sarjana Komunikasi Indonesia, 2025)
The rapid advancement of digital technology has transformed business practices worldwide, yet significant disparities remain in digital access and literacy, particularly among women entrepreneurs in urban Indonesia. This study examines the challenges faced by women-owned Micro, Small, and Medium Enterprises (MSMEs) in South Jakarta, highlighting the persistent gender and digital gaps that hinder inclusive economic development. Utilizing a combination of qualitative methods, including focus group discussions and in-depth interviews, the research investigates the barriers to digital adoption, such as limited digital literacy, cultural norms, and infrastructural constraints. Grounded in the Technology Acceptance Model (TAM) and principles of inclusive development, the study emphasizes the importance of context-specific communication strategies and community-driven solutions to foster empowerment and gender equity in digital transformation. Findings reveal that while government initiatives like the Jakpreneur program have provided essential training and resources, a gap persists in tailored, participatory approaches that address women’s unique needs and socio-cultural realities. The research advocates for strengthening community-based digital literacy programs, peer learning models, and mentorship schemes that leverage local knowledge and social networks. By bridging the digital divide, these strategies aim to bolster women entrepreneurs’ capacity to leverage digital platforms, expand market access, and sustain business growth. Ultimately, promoting inclusive development communication is vital for transforming digital inclusion from mere policy rhetoric into tangible empowerment outcomes, ensuring that women entrepreneurs in Jakarta Selatan are active agents in Indonesia’s digital economy.